Functional characteristics of the frontal cortex during the verbal fluency task in subthreshold depression: A fNIRS study - Liu, Jingxuan; Hu, Yuhan; Zong, Boyi; Wang, Shiyu; Zheng, Yifan; Guo, Dongxi; Shi, Chengchao; Cai, Ruijin; Li, Lin (Journal of affective disorders, 2025)
Subthreshold depression (SD), a recognized prodromal stage and major risk factor for major depressive disorder (MDD). Dysfunction of the frontal lobe is associated with the emergence and progression of depression. This study aims to systematically examine the functional characteristics of the frontal cortex in SD, including activation, functional connectivity (FC), and network topology properties. Using functional near-infrared spectroscopy (fNIRS) during verbal fluency tasks (VFT), the relative concentration of oxyhaemoglobin in the frontal cortex was measured in 70 female subjects with SD and 73 matched healthy controls. The SD subjects demonstrated reduced dorsolateral prefrontal cortex activation. FC analyses indicated weakened frontal cortex connectivity with adjacent regions and disrupted interhemispheric connectivity, alongside enhanced long-distance and edge frontal connectivity. Graph theory revealed functional network abnormalities of the frontal cortex in SD: decreased overall clustering coefficient (Cp), left-hemisphere Cp with increased global efficiency, and diminished right-hemisphere assortativity. Crucially, overall frontal Cp correlated with depressive symptom severity and showed predictive value for SD. During the VFT, SD subjects exhibited reduced frontal cortex activation, altered FC patterns, and functional network abnormalities. This study was the first to report that the Cp of the overall frontal cortex has the potential for prediction in SD. Our findings elucidate SD neuropathology and establish a foundation for early MDD diagnosis. •We systematically investigated activation, FC, and functional network patterns of the frontal cortex in SD.•SD showed weakened frontal cortex connectivity with adjacent regions and interhemispheric disruption.•SD exhibited increased FC in long-distance and edge frontal cortex areas.•Altered global network topology parameters in the overall, left, and right frontal cortex in SD.•The overall frontal Cp correlates with symptom severity and demonstrates predictive utility for SD.